Enhancement of Tissue Plasminogen Activator-Catalyzed Plasminogen Activation by Escherichia coii S Fimbriae Associated with Neonatal Septicaemia and Meningitis - Parkkinen, Jaakko; Hacker, Jörg; Korhonen, Timo K (Thrombosis and Haemostasis, 1991)
The effect of Escherichia coli strains isolated from blood and cerebrospinal fluid of septic infants on plasminogen activation was studied. These strains typically carry a filamentous surface protein, S fimbria, that has formerly been shown to bind to endothelial cells and interact with plasminogen. The bacteria effectively promoted plasminogen activation by tissue plasminogen activator (t-PA) which was inhibited by s-aminocaproic acid. A recombinant strain expressing S fimbriae accelerated t-PA-catalyzed plasminogen activation to a similar extent as did the wild-type strains whereas the nonfimbriate recipient strain had no effect. After incubation with t-PA and plasminogen, the S-fimbriate strain displayed bacterium-bound plasmin activity whereas the nonfimbriate strain did not. Bacterium-associated plasmin generation was also observed with a strain expressing mutagenized S fimbriae that lack the cell-binding subunit SfaS but not with a strain lacking the major subunit SfaA. Both t-PA and plasminogen bound to purified S fimbriae in a lysine-dependent manner and purified S fimbriae accelerated t-PA-catalyzed plasminogen activation. The results indicate that E. coli S fimbriae form a complex with t-PA and plasminogen which enhances the rate of plasminogen activation and generates bacterium-bound plasmin. This may promote bacterial invasion and persistence in tissues and contribute to the systemic activation of fibrinolysis in septicaemia.